2007
DOI: 10.1177/154405910708600412
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF-κB in TNF-α-induced COX-2 Expression in Synovial Fibroblasts from Human TMJ

Abstract: In the temporomandibular joint (TMJ) synovium, cyclo-oxygenase-2 (COX-2) expression has been believed to be directly related to joint pain and synovitis. Here we investigated the role of Nuclear Factor kappaB (NF-kappaB) in the regulation of COX-2 expression in synovial fibroblasts from human TMJ induced by tumor necrosis factor-alpha (TNF-alpha). By reverse-transcriptase/polymerase chain-reaction (RT-PCR) and Western blotting analysis, TNF-alpha induced a dose- and time-dependent increase in COX-2 expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…*p < 0.05 and **p < 0.01, compared with the saline control group. expression [35,36]. The current findings using UPLC-Q/TOF coupled with a dual-luciferase reporter assay for NF-B inhibitor screening was in accord with previous reports [25].…”
Section: Confirmation Of Anti-inflammatory Compounds From a Scholarisupporting
confidence: 93%
“…*p < 0.05 and **p < 0.01, compared with the saline control group. expression [35,36]. The current findings using UPLC-Q/TOF coupled with a dual-luciferase reporter assay for NF-B inhibitor screening was in accord with previous reports [25].…”
Section: Confirmation Of Anti-inflammatory Compounds From a Scholarisupporting
confidence: 93%
“…Proteolytic degradation of the matrix can also release immobilised cytokines such as interleukin (IL)-1β and IL-6 and tumour necrosis factor (TNF) which in turn further induce cytokine expression and secretion of matrix-degrading enzymes from chondrocytes, thus propagating tissue breakdown (David et al, 2007;Martel-Pelletier, 1999). These effects are largely mediated by nuclear transcription factors such as nuclear factor-kappaB (NF-κB), which has been shown to induce expression of inflammatory cytokines, matrix metalloproteinases (MMPs), cyclooxygenase-2 (COX-2), as well as adhesion molecules (ICAM-1, VCAM-1 and E-selectin) implicating NF-κB in the recruitment of leukocytes (Ke et al, 2007;Miagkov et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…According to the signaling pathway described above, it is possible that the decrease of NF-B activation by vaspin may be due to the inhibitory effects of vaspin on the phosphorylation of Akt. Some inflammatory mediators including VCAM-1, ICAM-1 [37], e-selectin [12], COX-2 [16], MCP-1 [1], TF [15] and PAI-1 [17] are induced by the activation of JNK, p38, or NF-B. In the present study, we also found that TNF- induced the activation of JNK, p38, and NF-B, the protein expression of VCAM-1, ICAM-1, e-selectin and COX-2, and the mRNA expression of MCP-1, TF and PAI-1.…”
Section: Discussionmentioning
confidence: 99%